Tumor-biology and current treatment of skull-base chordomas - (:unkn) unknown (SPRINGER-VERLAG WIEN, 2008)
Chordomas are rare, slow growing tumors of the axial skeleton, which derive from the remnants of the fetal notochord. They can be encountered anywhere along the axial skeleton, most commonly in the sacral area, skull base and less commonly in the spine. Chordomas have a benign histopathology but exhibit malignant clinical behavior with invasive, destructive and metastatic potential. Genetic and molecular pathology studies on oncogenesis of chordomas are very limited and there is little known on mechanisms governing the disease. Chordomas most commonly present with headaches and diplopia and can be readily diagnosed by current neuroradiological methods. There are 3 pathological subtypes of chordomas: classic, chondroid and dedifferentiated chordomas. Differential diagnosis from chondrosarcomas by radiology or pathology may at times be difficult. Skull base chordomas are very challenging to treat. Clinically there are at least two subsets of chordoma patients with distinct behaviors: some with a benign course and another group with an aggressive and rapidly progressive disease. There is no standard treatment for chordomas. Surgical resection and high dose radiation treatment are the mainstays of current treatment. Nevertheless, a significant percentage of skull base chordomas recur despite treatment. The outcome is dictated primarily by the intrinsic biology of the tumor and treatment seems only to have a secondary impact. To date we only have a limited understanding this biology; however better understanding is likely to improve treatment outcome. Hereby we present a review of the current knowledge and experience on the tumor biology, diagnosis and treatment of chordomas.
Keywords: Chordoma; chondrosarcoma; skull base; operative technique; Gamma-Knife; radiation therapy; FINE-NEEDLE-ASPIRATION; LOW-GRADE CHONDROSARCOMAS; PROTON RADIATION-THERAPY; TERM-FOLLOW-UP; AGGRESSIVE MICROSURGICAL RESECTION; MULTIDISCIPLINARY TEAM-APPROACH; GIANT ECCHORDOSIS-PHYSALIPHORA; CHARGED-PARTICLE IRRADIATION; TRANS-SPHENOIDAL SURGERY; NOTOCHORDAL CELL TUMORS